2021
DOI: 10.1111/apv.12317
|View full text |Cite
|
Sign up to set email alerts
|

The Belt and Road Initiative as Multiple Geographies of Knowledge Production

Abstract: The Belt and Road Initiative (BRI) has attracted wide scholarly attention. However, discussions among social scientists on BRI have largely premised on the academic infrastructure in English language contexts. Academic research on BRI in China has often been only briefly mentioned as background information in English language publications. This disjuncture between scholarship on BRI inside and outside China reflects the multiple geographies of BRI. Thinking through BRI in English and Chinese scholarship, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The Chinese government has invested heavily in framing Belt and Road as a ‘dialogue of civilisations’, proclaiming that all civilisations are equal and deserve ‘mutual respect’ (Winter, 2022a). But as Yang (2021) notes, as these discourses become structured around particular forms of scholarly research and cultural policy, distinct asymmetries can be observed. In this case I would emphasise the multiple imbalances across the contemporary political landscape, the histories being studied, and across the technologies being used to record and interpret them.…”
Section: As History Connects the Digital Dividesmentioning
confidence: 99%
“…The Chinese government has invested heavily in framing Belt and Road as a ‘dialogue of civilisations’, proclaiming that all civilisations are equal and deserve ‘mutual respect’ (Winter, 2022a). But as Yang (2021) notes, as these discourses become structured around particular forms of scholarly research and cultural policy, distinct asymmetries can be observed. In this case I would emphasise the multiple imbalances across the contemporary political landscape, the histories being studied, and across the technologies being used to record and interpret them.…”
Section: As History Connects the Digital Dividesmentioning
confidence: 99%